Busana dan Identitas Mahasiswa Muslim: Analisis Fenomena Stecu dari Sudut Pandang Islam dan Psikologi Sosial - Loka, Pita; S, Surawan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
In this study, “foam” is defined as a style of self-carry, attitude, gesture, and emotional interaction, rather than physical clothing. This study examines the phenomenon of “Stecu” (Stelan Cuek) among Muslim students, which emerged from Faris Adam’s song in March 2025. “Stecu” refers to the attitude of being shy and keeping one’s distance (selling expensive) when approached by the opposite sex. This phenomenon was analyzed from an Islamic and social psychology perspective using a qualitative approach with the analysis of social media content, particularly TikTok, which is relevant to Stecu’s self-boundaries, self-esteem, and lifestyle. Study results show that Stecu serves as a form of self-esteem defense, with narratives such as “indifferent gini originally wanted, just more self-defense aja.” Stecu has also evolved into a lifestyle, rather than just a trend, which reflects the internalization of values among Muslim students. Furthermore, Stecu is a mechanism of self-boundaries and empowerment, where an indifferent attitude is considered essential to protect oneself and filter people out in a dangerous world. From an Islamic perspective, Stecu aligns with the principles of iffah (maintaining honor) and muru’ah (maintaining dignity), as well as the recommendation not to approach adultery. From the social psychology side, Stecu is a social strategy for controlling others’ perceptions and maintaining personal integrity, in line with self-image formation theory. In conclusion, the Stecu phenomenon constitutes a harmonious identity strategy, fusing Islamic values of honor with the psychological need to build self-esteem and healthy constraints in the digital age.